A Nanoporous Carbon‐MXene Heterostructured Nanocomposite‐Based Epidermal Patch for Real‐Time Biopotentials and Sweat Glucose Monitoring. (18th September 2022) - Zahed, Md Abu; Sharifuzzaman, Md; Yoon, Hyosang; Asaduzzaman, Md; Kim, Dong Kyun; Jeong, Seonghoon; Pradhan, Gagan Bahadur; Shin, Young Do; Yoon, Sang Hyuk; Sharma, Sudeep; Zhang, Shipeng; Park, Jae Yeong
Abstract: Despite substantial progress in the development of wearable and flexible monitoring systems that conform to the epidermis, most designs focus on either physiological signs such as the electrocardiogram (ECG) results, respiration rate, or metabolites, and ignore the dynamic fluctuations of pH and temperature in sweat during on‐body tests. An advanced butterfly‐inspired hybrid epidermal biosensing ( bi ‐HEB) patch is presented here, which is interfaced with a custom‐developed miniaturized monitoring system. The patch incorporates a novel transducing layer of nanoporous carbon and MXene (NPC@MXene) for sensitive and durable detection of biomarkers in sweat. The bi ‐HEB patch is composed of a glucose biosensor accompanied by pH and temperature sensors to precisely quantify glucose as well as two biopotential electrodes, allowing real‐time recording of electrophysiological (EP) signals. The NPC@MXene‐based glucose biosensor demonstrates an excellent sensitivity of 100.85 µAmm −1 cm −2 within physiological levels (0.003−1.5 mm ), and variations in pH and temperature during on‐body perspiration monitoring are calibrated by employing a correction approach. In parallel, the EP electrodes exhibit skin‐electrode contact impedance and biopotential signals similar to those of conventional Ag/AgCl electrodes. Finally, the bi ‐HEB patch integrated wearable system is used to accurately monitor sweat glucose and ECG of human subjects participating in indoor physical activities. Abstract : In‐depth investigations of electrophysiological parameters, ECG, EMG, EEG, and temperature, with precise glucose level determination using an integrated multimodal epidermal patch have been performed in this work. The NPC@MXene‐based electrochemical sensors exhibit high sensitivities and selectivity, including long‐term stabilities. As a portable smart healthcare monitoring device, the bi ‐HEB patch is successfully paired with a miniaturized PCB to assess glucose leve and ECG of individuals.